Quiste de la bifurcación mandibular bucal en el paciente pediátrico: reporte de caso clínico y revisión de la literatura - Rivas Almonte, Ursula Ofelia (2024)
A mandibular buccal bifurcation cyst is an inflammatory odontogenic cyst that usually occurs on the buccal aspect of the permanent mandibular first or second molar and it occurs at an early age. The aim of present study is to report a case of mandibular buccal bifurcation cyst (MBBC) detected in a male pediatric patient. The main findings of this entity are reviewed and described. Clinically, slight effacement of vestibular sulcus base at the level of the first mandibular molar on the left side. A cone beam computed tomography was performed and revealed a hypodense image with defined limits, which conditions the displacement of the first mandibular molar on the left side toward the lingual cortex and the erosion of the buccal cortical bone (axial section). The lesion was surgically removed through enucleation, curettage, and bone grafting. The diagnosis of MBBC was confirmed by histological análisis.